The effect of using the Bransford model (IDEAL) on students' ability to solve health problems (Journal of the College of Basic Education, 2022)
The goal of health education is to prepare the learner to assume individual and social responsibility to deal appropriately in daily life, to face new health problems and situations, and to find appropriate solutions.